IgG4-related disease mimicking gynecologic malignancy - Rachel R. Pacyna; Nicole A. Cipriani; Melvy S. Mathew; Josephine S. Kim (Elsevier, 2023)
Immunoglobulin G4 (IgG4) related disease is a systemic disease that causes fibrosis, tumor-like nodules, and lymphoid hyperplasia with infiltration of IgG4 positive plasma cells. It can manifest in many organ systems; however, there are few cases that report gynecologic organ involvement. It is crucial to correctly diagnose IgG4-related disease versus malignancy because the former is treated with glucocorticoids or rituximab. In this case report, we describe two patients in which IgG4-related disease mimics gynecologic cancer. In the first case, an 85 year old woman presented with diffuse lymphadenopathy and a uterine mass concerning for malignancy. Biopsies were negative for carcinoma. Inguinal lymph node biopsy demonstrated IgG4 positive plasma cells and the patient was treated with rituximab therapy given concurrent severe rheumatoid arthritis. In the second case, a 35 year old woman under surveillance for Stage IB2 squamous cell carcinoma of the cervix (status post definitive chemoradiation therapy) presented with fluorodeoxyglucose (FDG) avid paraaortic lymph nodes on positron emission tomography (PET) imaging with subsequent negative paraaortic lymph node biopsies. Serial imaging and biopsies remained inconclusive despite ongoing diffuse lymphadenopathy and clinical concern for recurrence. Supraclavicular lymph node excision was performed which demonstrated lymphoid hyperplasia with increased IgG4 plasma cells and no evidence of carcinoma, supporting the diagnosis of IgG4-related disease. The patient was treated with high dose steroids with clinical improvement and resolution of abnormal imaging findings. We demonstrate that IgG4-related disease can present with FDG-avid lesions on PET imaging and lymphadenopathy that mimics primary or recurrent gynecologic malignancy. While rare, we conclude the IgG4-related disease is an important differential diagnosis to consider in the workup of primary or recurrent gynecologic malignancy and highlights the value of PET imaging to identify unusual patterns of lymphadenopathy and guide histologic confirmation of disease.